VHL mutation as a cause of three generations familial pheochromocytoma - Mari Carmen Moran-Espinosa; Héctor Diaz-García; Rocío Sánchez-Urbina; Javier T. Granados-Riveron; Miriam Deyanira Rodriguez-Piña; Ángeles Leyda Avilés-García; Miguel Ángel Rubio-Leal; Karla Ariadna Martínez-Camacho; Hugo Mendieta-Zeron (Egyptian Journal of Medical Human Genetics, 2024)
Abstract Background Pheochromocytoma is a rare disease, and its familial occurrence is quite uncommon. The aim of this paper is to report a three-generation phenotypical expression of a case familial occurrence of pheochromocytoma. Case presentation A 25-year-old female, with a history of adrenalectomy for pheochromocytoma, arrived at the shock room during her third pregnancy with an adrenergic crisis and hypoglycemia. To prevent perinatal complications, the patient was stabilized and the newborn was delivered through a Kerr-type cesarean section. A detailed history revealed that the paternal grandfather of the patient had an unilateral pheochromocytoma, whereas her paternal uncle had a bilateral pheochromocytoma. Additionally, a brother of the patient presented a unilateral pheochromocytoma. Amplicons for PCR assays were designed to span the protein-coding segments of the three Von Hippel–Lindau (VHL) exons, and the PCR products were sequenced using the Sanger method. In the trace of exon 3, we detected in the sample of the proband a heterozygous guanine to adenine transition (NM_000551.4 c. 552G > A) within the protein-coding segment of exon 3 of the VHL gene, which leads to a substitution of the arginine residue at position 161 by a glutamine residue in the encoded peptide (NP_000542.1p.R161Q). This mutation was absent in two unaffected daughters. Conclusion A VHL mutation was suspected and confirmed in this family that was not transmitted to a fourth generation. This case illustrates the importance of molecular genetics methodologies to assist genetic counseling in cases of pheochromocytoma where familial aggregation is presumed.